Etika Pelaksanaan Konseling Berbasis Online dengan Pemanfaatan Media dan Teknologi pada Masa Pandemi Covid-19 - Mardy Handika; Happy Karlina Marjo (Jurnal Paedagogy, 2022)
This study aims to describe the ethics of implementing online-based counseling using media and technology during the Covid-19 pandemic. This research method uses literature review by collecting reading materials from various sources with readings, comparing theories and research results regarding the use of technology media in the implementation of counseling, which are then analyzed descriptively. The result of this literature review is that the implementation of guidance and counseling using media and technology provides advantages and disadvantages. The advantages are related to the convenience obtained by BK / Counselor teachers in pre, implementation and post implementation of BK activities related to administration or guidance and counseling services. While the disadvantages are regarding public trust regarding the competence of implementing online counseling and the limitations of the media in its implementation, so that the maximum application of ethics in the implementation of online counseling is needed in order to anticipate the losses incurred.